Desmoid Tumor of the Abdominal Wall: A Case Report - Arzoo, Shabera; Akter, Mst Shamima; Afroz, Saima; Rahman, Md Ataur; Akther, Maher (Eastern Medical College Journal, 2023)
Desmoid tumors alternatively known as aggressive fibromatosis are benign myofibroblastic neoplasms originating from the muscle aponeurosis and classified as deep fibromatoses and these tumors are non-cancerous growth that occurs in the connective tissue. These tumors constitute 3% of all soft tissue tumors and 0.03% of all neoplasms and they occur usually between the age group of 20-40 years with a strong prevalence among women with fertile age group. In female patients presenting a tumor of the lower abdominal wall especially after cesarian section, an endometriotic tumor as well as an aggressive desmoid tumor should be considered. Symptoms in correlation with the monthly period can facilitate the presurgical differentiation between endometriosis and fibromatosis. Ultrasound reveals the typical location of both tumors and its remarkable sonographic appearance. In the clinical practice, the desmoid fibromatosis of the lower abdominal wall is a very rare disease. We present a case of a 19-year-old pregnant and discuss diagnostic and therapeutic options by literature review. With the knowledge of the prognosis of the desmoid fibromatosis and the respective treatment options including wait and see, complete surgical resection with macroscopically free margins and adjuvant approaches is essential to avoid further interventions and progression of the locally destructive tumor. EMCJ. July 2022; 7(2): 28-31